All-Polymer Solar Cells and Photodetectors with Improved Stability Enabled by Terpolymers Containing Antioxidant Side Chains - Zhang, Chunyang; Song, Ao; Huang, Qiri; Cao, Yunhao; Zhong, Zuiyi; Liang, Youcai; Zhang, Kai; Liu, Chunchen; Huang, Fei; Cao, Yong (Nano-Micro Letters, 2023)
It is of vital importance to improve the long-term and photostability of organic photovoltaics, including organic solar cells (OSCs) and organic photodetectors (OPDs), for their ultimate industrialization. Herein, two series of terpolymers featuring with an antioxidant butylated hydroxytoluene (BHT)-terminated side chain, PTzBI-EHp-BTBHTx and N2200-BTBHTx (x = 0.05, 0.1, 0.2), are designed and synthesized. It was found that incorporating appropriate ratio of benzothiadiazole (BT) with BHT side chains on the conjugated backbone would induce negligible effect on the molecular weight, absorption spectra and energy levels of polymers, however, which would obviously enhance the photostability of these polymers. Consequently, all-polymer solar cells (all-PSCs) and photodetectors were fabricated, and the all-PSC based on PTzBI-EHp-BTBHT0.05: N2200 realized an optimal power conversion efficiency (PCE) approaching 10%, outperforming the device based on pristine PTzBI-EHp: N2200. Impressively, the all-PSCs based on BHT-featuring terpolymers displayed alleviated PCEs degradation under continuous irradiation for 300 h due to the improved morphological and photostability of active layers. The OPDs based on BHT-featuring terpolymers achieved a lower dark current at − 0.1 bias, which could be stabilized even after irradiation over 400 h. This study provides a feasible approach to develop terpolymers with antioxidant efficacy for improving the lifetime of OSCs and OPDs. Highlights: 1 Two series of terpolymers with improved photostability were realized by the introduction of appropriate ratio of antioxidant butylated hydroxytoluene unit containing side chains. 2 All-polymer solar cells and organic photodetectors (OPDs) with these terpolymers as both donors and acceptors have been prepared with simultaneously improved efficiency and stability. 3 A feasible approach to develop terpolymers with antioxidant efficacy for improving the lifetime of organic solar cells and OPDs is proposed.